Sustainable development of apple snack formulated with blueberry juice and trehalose - Castagnini, Juan Manuel (2021)
Novel products that carry concrete and relevant health benefits, with texture and flavor not substantially different from already available products, are generally well accepted by consumers. Vacuum impregnation is a non-thermal technology that allows the enrichment of fruit with different ingredients in solution. The characteristic of the resulting product is a combination of both the solid matrix and the impregnation solution. This work aimed at: (i) evaluating the effect of trehalose on anthocyanin retention after drying of apple snacks vacuum impregnated with blueberry juice; (ii) modelling the air-drying kinetic, proposing an image analysis approach to monitor the drying process. Four mathematical models successfully fitted the drying experimental data, obtainingequations that could be used in the implementation of this process at industrial scale. The drying kinetics of samples impregnated with blueberry juice and trehalose were faster when compared to the control sample. Samples impregnated with blueberry juice and 100 g/kg of trehalose retained nearly four times more anthocyanin after drying when compared to the control.